Carbon dots derived from folic acid as an ultra-succinct smart antimicrobial nanosystem for selective killing of S. aureus and biofilm eradication. (31st October 2022) - Yu, Meizhe; Guo, Xiuzhi; Lu, Haojie; Li, Peili; Huang, Ruobing; Xu, Chunning; Gong, Xuedong; Xiao, Yuhong; Xing, Xiaodong
Abstract: Developing efficient and safe approach to counteract the bacterial infections has become an urgent clinical challenge. In this work, we report folic acid derived carbon dots (FA-CDs) prepared by a one-step pyrolysis method. The FA-CDs can respond to the environmental stimuli of bacterial infections and acquire antimicrobial capacity "on demand" as a simple and effective antimicrobial nanosystem. The assays on antibacterial properties and mechanism show that FA-CDs are able to induce the gradual increase of intracellular reactive oxygen species (ROS) levels in bacteria under the simulated acidic environment and display pH-responsive biocidal activity. In a neutral condition, FA-CDs have no antibacterial activity, which will be conducive to mitigating the rise of bacterial drug resistance. The responsive antibacterial behavior can be attributed to that FA-CDs exhibit distinctive oxidase-like and peroxidase-like activity under acidic stimuli and inhibit the superoxide dismutase activity in bacteria cells, causing the accumulation of intracellular ROS. Meanwhile, FA-CDs can selectively kill Gram-positive bacterium S. aureus and remove mature biofilms. Besides, the in vitro and in vivo experiments demonstrate that FA-CDs possess excellent biocompatibility, and show remarkable therapeutic effect on the S. aureus -infected back wound models of mouse, which are crucial for clinical applications. Thus, this study highlights the potential application of FA-CDs as an ultra-succinct smart antimicrobial nanosystem for coping with infections caused by S. au reus in the clinical setting, and will bring about a new perspective on developing antimicrobial CDs. Graphical abstract: Image 1